2016
DOI: 10.1021/acs.estlett.6b00036
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of New Delhi Metallo-β-lactamase Genes (blaNDM-1) from a Wastewater Treatment Plant to Its Receiving River

Abstract: The emergence and spread of NDM-1 (New Delhi metallo-β-lactamase-1) are of great concern to public health. Our previous study reported the occurrence and persistence of NDM-1 genes in wastewater treatment plants (WWTPs). In this study, the occurrence and fate of NDM-1 genes and host bacteria were investigated in a WWTP discharge-receiving river. A considerable level of NDM-1 genes occurred in the receiving river, whereas no NDM-1 genes were detected upstream of the WWTP. This finding together with the DNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…In this case, upstream biofilm samples yielded negative results for the bla NDM gene, thus suggesting that the treated effluent is likely to be responsible for the presence of this gene at downstream locations. This is consistent with findings by Yang and coworkers, who found that the prevalence of bla NDM‐1 in river water is directly linked to WWTP effluent discharges (Yang, Mao, Zhou, Wang, & Luo, ).…”
Section: Discussionsupporting
confidence: 92%
“…In this case, upstream biofilm samples yielded negative results for the bla NDM gene, thus suggesting that the treated effluent is likely to be responsible for the presence of this gene at downstream locations. This is consistent with findings by Yang and coworkers, who found that the prevalence of bla NDM‐1 in river water is directly linked to WWTP effluent discharges (Yang, Mao, Zhou, Wang, & Luo, ).…”
Section: Discussionsupporting
confidence: 92%
“…Multiple variants of bla NDM have been identified in clinical and environmental samples [33]. Our results further supplement previous studies that show NDM-1 to be widely distributed in wastewater in China [20,34,35]. We also found that NDM-5, which exhibits increased resistance to carbapenems and broad-spectrum cephalosporins [33], was also highly prevalent in the collected samples.…”
Section: Discussionsupporting
confidence: 88%
“…Aside from human-populated environments, CR can also spread into the natural milieu, including aquatic environments [42,[56][57][58]. CRGs, such as bla NDM-1 , bla KPC-2 , and bla OXA-58 , have also been reported in known environmental bacteria, such as Acinetobacter johnsonii [59] and Acinetobacter towneri [60].…”
Section: Epidemiology and Distribution Of Carbapenem Resistancementioning
confidence: 99%